A3_4 Tree-location - Routledge, Hannah; Meggi, Dikshita; Yeo, Adam; Lewis, Jacob (Physics Special Topics, 2021)
In this paper it is explored whether or not the food items available to eat in the Nintendo game ’Animal Crossing: New Horizons’ contain enough energy for the character to be able to dig a tree out of the ground, assuming that they already have the muscle mass to do so. It is found that the total work done to lift the tree out of the ground is 18.63kJ, meaning that each variety of food within the game are able to provide enough energy to lift the tree.